Evaluating the Impact of QIZ Protocol on Egypt’s Textile and Clothing Sector - ElGhouty, Amal (Archives of Business Research, 2020)
Since the enforcement of the Qualified Industrial Zones (QIZ) protocol signed by Egypt in December 2004, the number of QIZ companies have steadily increased, reaching 1048 companies in 2019. Additionally, the QIZ textile and clothing exports have increased, as well as its percentage from Egypt’s total exports to the USA. The paper seeks to study and explore the conditions and circumstances that induced Egypt to sign the QIZ agreement. The paper will then review several previous studies on the impact of the agreement on the Egyptian textile and clothing sector. We will also review the trend of the number of QIZ companies. Additionally, in order to assess whether the QIZ protocol have a positive impact on the textile and apparel sector, we will evaluate the trends in the Egyptian textile and apparel exports to the USA and what percentage does these exports constitute from Egypt’s total exports.